PENGARUH INSENTIF KINERJA, USAHA DAN KOMPLEKSITAS TUGAS TERHADAP KUALITAS AUDIT JUDGEMENT - Sugiarto Sugiarto (Universitas Muhammadiyah Semarang, 2008)
This research examines the effect of performance incentives, effort and task complexity on the quality of audit judgement. This research replicated research model which had been done by Sanusi and Iskandar (2007), The respondents consisted of student in Pendidikan Profesi Akuntan Diponegoro University Semarang, Central Java.Experimental research design 3 x 1 was used to examine the hypotheses. Using purposive sampling technique, the subjects were classified into three groups, namely financial incentives groups, non-financial incentives groups, and a control group with no incentives. Each group was required to perform high and low task complexity. 45 students participated in this experiment. The results of the experiment were then analyzed using T- Test or Mann Whitney Test and moderated regression analysis (MRA).The results showed that among five hypotheses only one hypothesis was rejected. First, this research found that financial incentives group and non-financial incentives group performed better quality of audit judgment than group with no incentives. Secondly, subject within financial incentives group and non-financial incentives group exerted more effort than subject with no incentives. Third, this research provided strong evidence that the relation of efforts and the quality of audit judgment is moderated by task complexity. Fourth, this research showed that when task complexity is high, there is no different of audit quality performed by subject with high efforts and low efforts. And finally, this research failed to find that when task complexity is low, subject with high efforts will perform better quality of audit judgment than subject with low efforts.Keywords: Performance Incentives, task complexity, and the quality of Audit Judgement.